2020
DOI: 10.1017/s0954422420000104
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of dietary advanced glycation endproducts in the development of chronic non-infectious diseases: a narrative review

Abstract: Increasing clinical and experimental evidence accumulated during the past few decades supports an important role for dietary advanced glycation endproducts (AGE) in the pathogenesis of many chronic non-infectious diseases, such as type 2 diabetes, CVD and others, that are reaching epidemic proportions in the Western world. Although AGE are compounds widely recognised as generated in excess in the body in diabetic patients, the potential importance of exogenous AGE, mostly of dietary origin, has been largely ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 146 publications
(255 reference statements)
0
20
0
1
Order By: Relevance
“…The persistence of high serum glucose levels and oxidative stress result in advanced glycation ends (AGEs). The endogenous formation of AGEs occurs through several mechanisms, including the oxidation of amino acids, lipids, nucleic acids, and sugars, involved in the Maillard reactions, 80 and the polyol pathway, which is hyperactive in hyperglycaemic states 81 . The result is the production of highly reactive intermediates, which later interact with circulating proteins, amplifying the synthesis of these substances 82 …”
Section: Resultsmentioning
confidence: 99%
“…The persistence of high serum glucose levels and oxidative stress result in advanced glycation ends (AGEs). The endogenous formation of AGEs occurs through several mechanisms, including the oxidation of amino acids, lipids, nucleic acids, and sugars, involved in the Maillard reactions, 80 and the polyol pathway, which is hyperactive in hyperglycaemic states 81 . The result is the production of highly reactive intermediates, which later interact with circulating proteins, amplifying the synthesis of these substances 82 …”
Section: Resultsmentioning
confidence: 99%
“…α-DCs could be derived from reaction of MR, caramelization, or lipid peroxidation over 120 °C [7]. Puddings are prepared by heating at 85-95 °C for about 6 minutes [8]. The low cooking temperature may be another reason the low α-DCs content in puddings.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies found out that excessive AGEs exposure may cause variety of diseases including inflammation, aging, kidney disease, cardiovascular diseases, neurodegenerative diseases, diabetes, and cancer [3,6,7]. In this context, it is highly essential to reduce AGEs exposure by limiting exogen AGE intake [8] Diet is the main contributor of endogenous AGE exposure [9]. AGEs can be easily formed in foods due to MR, caramelization, sugar autooxidation and lipid peroxidation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Only about 10–30% of AGEs present in food are absorbed into the systemic circulation [ 11 ]. The mechanisms of the gastrointestinal absorption of AGEs, which have not been fully elucidated, depend on both the hydrolysis of glycated proteins and absorption of the resulting free amino acids or small peptides containing the AGEs [ 12 ]. The majority of food AGEs escape digestion and absorption and are delivered to the colon, where there is increasing evidence that they may modify local microbiota metabolism and modulate gut integrity.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent narrative review, we presented data from several small interventional trials looking at the effects of dAGE restriction ranging from a few weeks up to 1 year duration. These trials consisted essentially of changing the way of cooking food without modifying caloric and macronutrient intakes [ 12 ]. These trials demonstrated that a low AGE diet is associated with a reduction of circulating AGE markers such carboxymethyllysine (CML) and methylglyoxal (MG)-derivatives, as well as markers of inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%